Masterpieces from the Museum of Fine Arts Berne. - von Tavel, Hans Christoph; Nara Sogo Museum of Art, Nara; Kitayushu Municipal Museum of Art, Kitayushu (Tokyo : Daimaru Museum, 1993)
Amiet, Cuno ; Arp, Hans (Jean) ; Auberjonois, René ; Barraud, Maurice ; Berger, Hans ; Bill, Max ; Braque, Georges ; Brignoni, Serge ; Dali, Salvador ; Derain, André ; Friesz, Othon ; Giacometti, Alberto ; Giacometti, Augusto ; Giacometti, Giovanni ; Gimmi, Wilhelm ; Glarner, Fritz ; Hodler, Ferdinand ; Itten, Johannes ; Kandinsky, Wassily ; Klee, Paul ; Leger, Fernand ; Liebermann, Max ; Lohse, Richard Paul ; Masson, Andre ; Matisse, Henri ; Meyer-Amden, Otto ; Nebel, Otto ; Oppenheim, Meret ; Ozenfant, Amédée ; Picasso, Pablo ; Seligmann, Kurt ; Slevogt, Max ; Soutine, Chaim ; Tschumi, Otto ; Utrillo, Maurice ; Vallotton, Félix ; Vuillard, Edouard
German-Japanese
Masterpieces from the Museum of Fine Arts Berne, Daimaru Museum, Tokyo, 17 September - 12 October 1993 ; Nara Sogo Museum of Art, Nara, 27 October - 23 November 1993 ; Kitayushu Municipal Museum of Art, Kitayushu, 27 November 1993 - 9 January 1994
kunstcatalogus